Exploring the Role of Workplace Incivility and Social Anxiety Within Organizations - Aisyah, Aisyah; Josephine Jesajas, Thea Geneveva; Hendharsa, Angga (JURNAL MANAJEMEN MOTIVASI, 2025)
This study examines how workplace incivility influences turnover intention among Generation Z employees in Pontianak’s private sector, with social anxiety as a mediator. Using a quantitative survey of 137 permanent Gen Z employees and PLS-SEM analysis, results show that workplace incivility directly increases social anxiety and turnover intention. Social anxiety partially mediates the relationship, highlighting its psychological impact. These findings reveal the harmful effects of uncivil work environments on Gen Z’s mental health and job retention. The study emphasizes the need for supportive organizational climates to mitigate incivility and promote employee well-being.